Volume 2: 29th Computers and Information in Engineering Conference, Parts a and B 2009
DOI: 10.1115/detc2009-87073
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Health Management User Objectives Related to Diagnostic and Prognostic Metrics

Abstract: One of the most prominent technical challenges to effective deployment of health management systems is the vast difference in user objectives with respect to engineering development. In this paper, a detailed survey on the objectives of different users of health management systems is presented. These user objectives are then mapped to the metrics typically encountered in the development and testing of two main systems health management functions: diagnosis and prognosis. Using this mapping, the gaps between us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…This shows that the amplitude of the soft defect signature γ d d is very small and explains why such a defect is difficult to detect using reflectometry, as verified experimentally in [45]. Similar models have been presented and extended in [46,47] for a multiconductor transmission line.…”
Section: The Problem Of Soft Defect Detectionmentioning
confidence: 64%
“…This shows that the amplitude of the soft defect signature γ d d is very small and explains why such a defect is difficult to detect using reflectometry, as verified experimentally in [45]. Similar models have been presented and extended in [46,47] for a multiconductor transmission line.…”
Section: The Problem Of Soft Defect Detectionmentioning
confidence: 64%
“…It is important to note that the criticalities of different costs and maintenance operations vary for each stakeholder [9] and depend on whether the vehicle is operated in a civilian or a military environment [10]. Therefore, a correct estimation of the uncertainty requires identifying which costs and benefits are allocated to each stakeholder.…”
Section: Quantifying Uncertaintymentioning
confidence: 99%
“…Furthermore, health monitoring technology can underpin the transformation of manufacturers to service providers, meaning any CBA for IVHM must take into account the effect it can have on current and future contracts as well as the company's mid and long-term strategy [8]. Wheeler et al [13] identified the goals for different stakeholders according to their responsibilities: logistics, mission operation, maintenance and fleet management. These goals are then divided into those which can be achieved using diagnostic tools and those which need the use of prognostic tools.…”
Section: Identifying the Role Of Stakeholdersmentioning
confidence: 99%